MICROPROPAGATION OF KINNOW THROUGH NODAL EXPLANTS - TARU SHARMA; MOHD. KAMRAN KHAN; PRAGATI MISRA; P. K. SHUKLA (The Bioscan, 2012)
This study was conducted to develop protocol for micropropagation of kinnow from nodal explants. These nodal explants were cultured on MS medium fortified with different concentrations and combinations of BAP and NAA. Best shoot multiplication was obtained on MS medium supplemented with BAP (3 mg/L) and NAA (0.5 mg/ L). Transfer of shoots to a rooting medium induced highest percentage of rooting on MS supplemented with NAA (2.0 mg/L).